Atomistic Simulation of Anistropic Crystal Structures at Nanoscale - Fu, Jia (IntechOpen, 2019)
Multiscale simulations of atomistic/continuum coupling in computational materials science, where the scale expands from macro-/micro- to nanoscale, has become a hot research topic. These small units, usually nanostructures, are commonly anisotropic. The development of molecular modeling tools to describe and predict the mechanical properties of structures reveals an undeniable practical importance. Typical anisotropic structures (e.g. cubic, hexagonal, monoclinic) using DFT, MD, and atomic finite element methods are especially interesting, according to the modeling requirement of upscaling structures. It therefore connects nanoscale modeling and continuous patterns of deformation behavior by identifying relevant parameters from smaller to larger scales. These methodologies have the prospect of significant applications. I would like to recommend this book to both beginners and experienced researchers.